Law and identity in Israel : a century of debate / Nir Kedar ; translated by Haim Watzman. - Kedar, Nir (Cambridge studies in law and Judaism., 2019)
What makes Israeli law Israeli? Why is the word 'Jewish' almost entirely absent from Israeli legislation? How did Israel succeed in eluding a futile and dangerous debate over identity, and construct a progressive, independent, original and sophisticated legal system? Law and Identity in Israel attempts to answer these questions by looking at the complex bond between Zionism and the Jewish culture. Forging an original and 'authentic' Israeli law that would be an expression and encapsulation of Israeli-Jewish identity has been the goal of many Jewish and Zionist jurists as well as public leaders for the past century. This book chronicles and analyzes these efforts, and in the process tackles the complex meaning of Judaism in modern times as a religion, a culture, and a nationality. Nir Kedar examines the challenges and difficulties of expressing Judaism, or transplanting it into, the laws of the state of Israel.